IMPLIKASI PROGRAM CSR BANK TERHADAP PEMBERDAYAAN MASYARAKAT DI KOTA KUPANG - Debryana Y Salean; Chandy M Henukh (Journal of Management Small and Medium Enterprises (SMEs), 2020)
The purpose of this study is to analyze the implications of the Corporate Social Responsibility program of Indonesian Reserve Bank on community empowerment in the Sehati and Noetnana clusters of Fatukoa Village, Kupang City. This study uses a qualitative descriptive approach. In this study use SWOT analysis includes efforts to identify strengths, weaknesses, opportunities, and threats that determine company performance. The results from the SWOT analysis that the implementation of cluster development towards community empowerment showed that the cluster had more dominant strengths and opportunities so that it had a positive impact on cluster development, especially the empowerment of the community members of the cluster. Keyword :Klaster Sehati, Klaster Noetnana, CSR (Corporate Social Responsibility)